Cryptococcal lymphadenitis in HIV: A chance diagnosis by FNAC. Issue 5 (17th April 2012) - Bhuyan, Pallavi; Pattnaik, Kaumudee; Kar, Asaranti; Brahma, Rathish Chandra; Mahapatra, Smita
Abstract Cryptococcosis is a life threatening, opportunistic fungal disease in human immunodeficiency virus‐infected individual. Lymph node involvement as a presenting feature in Cryptococcosis is not a common manifestation. A prompt diagnosis is of utmost importance in this disseminated form of cryptococcosis. There are very few reports, however, of cryptococcal lymphadenitis as a presenting feature. We report here a case of cryptococcal lymphadenitis that was diagnosed by fine‐needle aspiration cytology of the involved cervical lymph node. Diagn. Cytopathol. 2013. © 2012 Wiley Periodicals, Inc.